Chronic Rhinosinusitis with Nasal Polyps: Clinical Features, Impact on Quality of Life and Treatment Approaches - a review - Piasecka, Natalia; Majewska, Melania; Miara, Natalia; Kadłubańska, Martyna; Strzyż, Joanna; Szydłowska, Dorota; Szpilczyńska, Karolina; Baraniecka, Aleksandra (Journal of Education, Health and Sport, 2026)
Introduction: Chronic rhinosinusitis with nasal polyps (CRSwNP) is a chronic inflammatory disease of the nasal cavity and paranasal sinuses characterized by bilateral nasal polyps, persistent symptoms, and a marked reduction in quality of life. The condition is commonly associated with type 2 inflammation and frequently coexists with asthma and aspirin-exacerbated respiratory disease. Aim: The aim of this review is to present current evidence-based approaches to the diagnosis and conservative and surgical management of chronic rhinosinusitis with nasal polyps. Materials and Methods: This narrative review is based on international guidelines, systematic reviews, and key clinical studies addressing the pathophysiology, diagnosis, and treatment of CRSwNP. Results: Diagnosis of CRSwNP requires chronic sinonasal symptoms lasting at least 12 weeks with objective confirmation of nasal polyps on endoscopy or imaging. First-line treatment includes long-term intranasal corticosteroids and saline irrigation, with short courses of systemic corticosteroids used in severe cases. Biologic therapies targeting type 2 inflammatory pathways are effective in selected patients with severe or refractory disease. Endoscopic sinus surgery remains an essential treatment option when medical therapy fails, providing significant symptom relief and improved quality of life. Conclusions: Optimal management of CRSwNP requires an individualized, stepwise approach integrating medical treatment, surgical intervention, and biologic therapy to achieve long-term disease control.